The drosophila Chmp1 protein determines wing cell fate through regulation of epidermal growth factor receptor signaling. Issue 8 (6th May 2014) - Valentine, Meagan; Hogan, Justin; Collier, Simon
<x xml:space="preserve">Abstract</x> BACKGROUND: Receptor down‐regulation by the multivesicular body (MVB) pathway is critical for many cellular signaling events. MVB generation is mediated by the highly conserved ESCRT (0, I, II, and III) protein complexes. Chmp1 is an ESCRT‐III component and a putative tumor suppressor in humans. However, published data on Chmp1 activity are conflicting and its role during tissue development is not well defined. RESULTS: We investigated the function of Drosophila Chmp1 and found that it is an essential gene. In the wing, loss of Chmp1 activity causes a cell fate change from intervein to vein, and interactions between Chmp1 and Drosophila Epidermal Growth Factor Receptor (DER) regulators suggest that Chmp1 negatively regulates DER signaling. Chmp1 knockdown also decreases Blistered expression, which is repressed by DER signaling. We find that Chmp1 protein localizes to the late endosome in Drosophila embryos, which is consistent with its effects on DER signaling resulting from its function in the ESCRT‐III complex. CONCLUSIONS: Drosophila Chmp1 negatively regulates DER signaling, likely through its role in MVB formation. Loss of Chmp1 activity in the Drosophila wing induces a cell fate change from intervein to vein that should provide a useful tool for future studies of ESCRT protein activity. Developmental Dynamics 243:977–987, 2014. © 2014 Wiley Periodicals, Inc.